ประสิทธิผลของการพัฒนาทักษะชีวิตไปยังความรู้และการป้องกันพฤติกรรมเสี่ยงทางเพศท่ามกลางนักเรียนหญิงโรงเรียนมัธยมศึกษา - แสนเมือง, ทิวาทิพย์; ชูศักดิ์, ทัศพร; นันทชัย, เบญจวรรณ; ไชยวงศ์, สันหวัช (Health Science, Science and Technology Reviews, 2015)
ประเมินทักษะชีวิตอิงโรงเรียนสำหรับนักเรียนหญิงโรงเรียนมัธยมอำเภอแม่สรวย จังหวัดเชียงราย ผ่านการออกแบบกึ่งการทดลองเฉพาะกลุ่มทดลองก่อนและหลังการแทรกแซงจำนวน 30 คน อิงตัวแปรสองระดับ ประกอบด้วย ความรู้และพฤติกรรมการป้องกันเป็นตัวชี้แนะสำหรับเนื้อหาโครงงาน ประเมินผ่านตัวแปรเหล่านี้ มีการเพิ่มขึ้นอย่างมีนัยสำคัญของตัวแปรทุกตัวเป็นเสมือนตัวตั้งต้นของการมีเพศสัมพันธ์อย่างปลอดภัย Effect of developing life skill toward knowledge and the prevention of risky sexual behaviors among female secondary school students Thiwathip Sanmuang1, Thasaporn Chusak2, Benjawan Nunthachai3, Sanhawat Chaiwong4* 1 Makawtom Health Promotion Hospital, Makawtom Subdistrict, Muang District, Chiangrai Province 57100 2 Wangkhang Health Promotion Hospital, Wangkhang Subdistrict, Pisalee District, Nakhonsawan Province 60220 3 Faculty of Health Science, Nation University, Lampang Province 52000 4* School of Medicine, University of Phayao, Phayao Province 56000 A school-based life skill for female secondary school students was evaluated in Maesuai district, Chiangrai province through a through a quasi-experimental pre–post intervention with 30 cases of an experimental group. Based on two levels of variables; knowledge and preventive behaviors were included as a guide for the content of the program. Evaluation was conducted following these categories. Significant increases in all of these variables recognized as precursors of safer sex were found in the experimental group.